Kajian IPAL Rumah Potong Ayam di PT. X Bali: Evaluasi Teknis, Analisis Dampak Lingkungan, dan Perumusan Strategi Pengelolaan - Mahendra, Cok Agung Andra; Nurhayati, Ervin (Universitas Tanjungpura, 2026)
PT. X Bali is a chicken-slaughtering industry in Tabanan Regency, Bali, and has been operating since 2008. The production process in this industry requires large amounts of air for washing, which ultimately produces liquid waste. The liquid waste produced has the potential to pollute the environment. This study aims to activate the liquid waste processing unit at PT's Wastewater Treatment Plant (IPAL). X Bali, analyze the impact on the environment, and develop a management strategy. The study was conducted by collecting data from the source of liquid waste production, including the amount produced, its characteristics, and the capacity of the liquid waste processing facility. The IPAL was evaluated from a technical standpoint, considering its suitability with the design criteria for each unit. The environmental impact evaluation was conducted by analyzing changes in the pollution index (PI) of the river receiving the IPAL effluent due to the pollutant load from the IPAL. Furthermore, through a SWOT analysis, a management strategy for the IPAL was formulated based on its current conditions. The results of the study showed that the efficiency of the IPAL PT. X Bali for TSS parameters is only 41%, while BOD, COD, oil & fat, and NH₃ parameters show efficiency above 90%. The results of the class 4 river water pollution index indicate that the water quality status of the Yeh Penet tributary in the study area is